Bratislava Statement: consensus recommendations for improving pancreatic cancer care. Issue 6 (13th November 2020) - Prades, Joan; Arnold, Dirk; Brunner, Thomas; Cardone, Antonella; Carrato, Alfredo; Coll-Ortega, Cristina; De Luze, Samuel; Garel, Pascal; Goossens, Maria E; Grilli, Roberto; Harris, Meggan; Louagie, Marleen; et al.
Abstract : Pancreatic cancer is one of the most lethal tumours, and it is the fourth cause of cancer death in Europe. Despite its important public health impact, no effective treatments exist, nor are there high-visibility research efforts to improve care. This alarming situation is emblematic of a larger group of cancer diseases, known as neglected cancers. To address the impact of these diseases, the European Commission-supported Innovative Partnership for Action Against Cancer launched a multi-stakeholder initiative to determine key steps that healthcare systems can rapidly implement to improve their response. A working group comprising 20 representatives from European medical societies, patient associations, cancer plan organisations and other relevant European healthcare stakeholders was organised. A consensus process based on the results of different studies, discussion of research outcomes, and development and endorsement of draft statements resulted in 22 consensus recommendations (the Bratislava Statement). The statement argues that substantial improvements can be achieved in patient outcomes by centralising pancreatic cancer care around state-of-the-art reference centres, staffed by expert multidisciplinary teams capable of providing high-quality care. This organisational model requires a specific care framework encompassing primary, palliative and survivorship care, and a policy environment prioritising the use of quality criteria and performance assessments as well as research investments dedicated to prevention, risk prediction, early detection and diagnosis. In order to address the challenges posed by neglected cancers in general and pancreatic cancer in particular, a specific control strategy tailored to this reality is required.